The Influence of Using Technology Based Information Systems in Increasing Profitability in Food Industry MSMEs in Mataram City - Widiawan, I Ketut Bayu; Akram, Akram (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the influence of the use of Technology-Based Information Systems (e-commerce) in increasing the Profitability of Food Industry MSMEs in Mataram City. This study uses a descriptive method with a quantitative approach. The type of data used is primary data. Primary data is collected directly from MSMEs that are the research samples. The methods used in data collection include interviews, questionnaires, and documentation. The population in the study is the Food Industry MSMEs in Mataram City with a sample of 80 MSMEs, with the sampling technique used is purposive sampling. The data analysis method in this study is simple linear regression processed with an analysis tool in the form of SPSS 18. The results of the study obtained are that the use of technology-based information systems produces a significant positive impact on the profitability of MSMEs in the food industry in Mataram City.